PENANGGULANGAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH KPK BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2002 - Krisnadi Yudiantara, I Gusti Ngurah Nyoman; Tuni Cakabawa L., Putu (Kertha Wicara : Journal Ilmu Hukum, 2013)
Indonesia has long been anticipating the occurrence of corruption. Such efforts havemore incentive to do from year to year, especially in 1998 when it entered the new order.This commission can be established by Law 30 of 2002 on the Corruption EradicationCommission, which is trying to find the truth based on scientific logic of normative side.KPK has to realize the vision and mission of Indonesian corruption free and duty andauthority in the inquiry, investigation and prosecution of corruption, and to monitor theimplementation of the state.
Keywords: KPK, crime, corruption, truth